Effect of sintering duration on structure and properties of Ni-Al metal-intermetallic composites produced by SPS - Tatiana Ogneva; Alexander Anisimov; Ruslan Kuzmin; Andrey Tyurin; Yulia Emurlaeva; Natalya Aleksandrova (Chimica Techno Acta)
The fabrication of Ni-Al based metal-intermetallic layered (MIL) composites is one of the actively developing directions in the production of materials for aircraft and space industries. Alternating hard intermetallic layers with ductile metal layers provides a unique combination of mechanical properties. In this study, metal-intermetallic layered composites consisting of Ni and nickel aluminides were fabricated using spark plasma sintering (SPS) of Ni and Al foils 100 and 25 μm in thickness, respectively. Samples sintered at 1100 °C for 0.5, 3, and 8 min were obtained. The purpose of this study was to fabricate Ni-Al MIL composites with increased strength properties using SPS technique and to investigate the effect of sintering duration on structure and properties. The structure of the samples sintered for 0.5 min consisted of Ni layers and intermetallic layers containing the sublayers with stoichiometric and Ni-rich B2 NiAl, L10 twinned martensite NiAl. The tensile strength of such composites was 485 MPa. The intermetallic layers in the sample sintered for 3 min have more Ni-rich NiAl, martensite NiAl, and Ni3Al phases, which promoted to an increase in tensile strength to 575 MPa. The sample sintered for 8 min consisted of Ni and a solid solution of Al in Ni and showed the highest tensile strength, 610 MPa, due to solid solution hardening in the interlayers. The samples did not break when applying bending load, which is the evidence of the good reliability and durability of the composites.